An Examination of the Associations Among Victimization, Mental Health, and Offending in Women. (June 2017) - Lynch, Shannon M.; DeHart, Dana D.; Belknap, Joanne; Green, Bonnie L.; Dass-Brailsford, Priscilla; Johnson, Kristine M.; Wong, Maria M.
This study examines mental health as a mediator of the victimization and offending link in women. We administered structured diagnostic interviews to 491 women in urban and rural jails in four geographic regions of the United States to obtain detailed lifetime mental health, substance use, victimization, and conviction history. Structural equation modeling (SEM) was used to examine associations among adult and childhood experiences of interpersonal violence, lifetime mental health and substance use disorders, treatment utilization, and total number of convictions. Lifetime mental health and substance use disorders mediated the relationship between childhood victimization and adversity and number of convictions, and between adult victimization and number of convictions. In addition, greater treatment utilization was significantly associated with number of convictions. The findings offer support for including mental health and treatment utilization in models of women's offending and conducting comprehensive mental health assessments of women entering jail.